IMPLEMENTASI KEBIJAKAN PEMBANGUNAN DAN PENGELOLAAN PERUMAHAN BAGI MASYARAKAT BERPENGHASILAN RENDAH DI RUSUNAWA KAMPUNG TIDAR KOTA MAGELANG - Guruh Wahyu Pamungkas (Jurnal Paradigma Multidisipliner (JPM), 2021)
This study aims to determine the implementation of housing development and management policy for low income communities in Kampung Tidar, South Magelang Subdistrict, Magelang City. This study uses a qualitative desciptive method and the data collection was conducted through in-depth interviews, focus group discussions, and documentation method. The purpose of this study is to describe the implementation of housing development policies for low income people in Rusunawa Kampung Tidar Magelang City. The results shows that the implementation of Rusunawa (simple rented flats) development and mangaement policy in Kampung Tidar has not been appropiate with expectation. The implementation of housing development policies for income earners in Rusunawa Tidar has not yet been approved as expected, obtained while still in the field found to find increasingly complex challenges. The management organization of Rusunawa Kampung Tidar is not good yet, because there is no economic empowerment for residents from related agencies in Magelang City government. Keywords : Implementation of Policy, Housing Policy, Socio Economic, Low Income Communities